PENGEMBANGAN DATA NAGARI TANJUNG GADANG MENUJU DESA DIGITAL - Yenni Kurniawati; Dina Fitria; Admi Salma (Pelita Eksakta, 2023)
Developing villages' data toward digital data is one of villages' government programs to improve the villages. The village's government needs collaboration with professional surveyors and data digital builders to achieve the goal, which the government is unable to provide. The Statistics Department provided the team to overcome the problems by giving training surveys to local residents and accompanying them to build Nagari Tanjung Gadang digital data.